Selection Of The Best Route For National Roads In Palembang City Through Ppp Financing Scheme With Analytical Hierarchy Process (AHP) Approach - Dali Kesuma Wicaksana*; Erika Buchari; Edi Kadarsa (Riwayat: Educational Journal of History and Humanities, 2023)
Government Cooperation with Business Entities or Kerjasama Pemerintah dan Badan Usaha (KPBU) is an alternative financing scheme in which part or all uses the resources of the business entity by considering the distribution of risks between the parties. Preserving the road network with a KPBU scheme on existing roads will greatly help achieve Palembang's integrated metropolitan and economic area. However, Determining the priority of road maintenance is one of the important tasks faced by decision-makers and is considered a complex multi-criteria problem. A system is needed to filter and sequence projects based on several criteria. Therefore, it is necessary to have a method regarding the determination of road priority that will be carried out maintenance so that it is right on target. This study proposed the Analytical Hierarchy Process (AHP) Method as a determinant of the order of priority for national road maintenance in Palembang City by the KPBU scheme. The approach taken in this research was to evaluate based on criteria of road condition, traffic volume, traffic accident rate, and volume capacity ratio. From the results of the analysis using the AHP approach, the volume capacity ratio was a top priority on the road criteria that must be considered. This was a bit contradictory to the selection of decisions by policymakers in the road maintenance process, where road condition factors are usually the most important consideration before carrying out repairs. Furthermore, the best route selection alternative for the KPBU scheme on the national road in the city of Palembang produces route 2, which was the top priority. These results showed the linearity between respondents' ratings and the volume capacity ratio as a criterion with top priority because route 2 had the highest volume capacity ratio value among other routes, 3.57. This respondent's assessment needs to be taken into consideration by policymakers because, if seen from the road conditions, these routes were in stable road conditions, but with a large enough traffic volume, it results in the need for road repairs taking into account the volume capacity ratio or road capacity.